2007
DOI: 10.1063/1.2713045
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature magnetoresistance in magnetic tunnel junctions with Fe3O4 electrode

Abstract: We report on the fabrication and spin-dependent transport properties of epitaxial Fe3O4∕MgO∕Co75Fe25 magnetic tunnel junctions (MTJs) grown on sapphire (00.1) substrates. The MTJs showed magnetoresistance (MR) ratios ranging from −14% to 10% at room temperature and a somewhat scattered resistance-area product (RA) ranging from 7×107to3×1010Ωμm2. The relationship between MR ratio and RA revealed a tendency for the MR ratio to go from positive to negative as RA increases. Because MTJs with fewer imperfections sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…The P value of material can be evaluated from a TMR ratio using Julliere's formula. 13 However, it is very sensitive to interface states at the ferromagnet/insulator interfaces in MTJ, [14][15][16] making it difficult to determine the P value. Also, the sign of b cannot be determined from a conductance curve in the PCAR measurement.…”
Section: Introductionmentioning
confidence: 99%
“…The P value of material can be evaluated from a TMR ratio using Julliere's formula. 13 However, it is very sensitive to interface states at the ferromagnet/insulator interfaces in MTJ, [14][15][16] making it difficult to determine the P value. Also, the sign of b cannot be determined from a conductance curve in the PCAR measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Even though very high P values (-80 %) have been observed in epitaxial magnetite films [5], the possibility to obtain full spin polarization in this material is still disputed [4,6]. The large number of recent publications on this topic underlines the high interest in this material [5][6][7][8][9][10][11][12][13][14][15][16], but the practical achievement of (the expected) high performances in functional spintronic devices like magnetic tunnel junctions (MTJ) incorporating Fe 3 O 4 has not been reached yet [9][10][11]13].…”
Section: Introductionmentioning
confidence: 99%
“…Thin Fe 3 O 4 films are mainly produced by pulsed laser deposition [10][11][12][13], magnetron sputtering [7-9, 14, 15], and molecular beam epitaxy [16]. We propose a simple and cost-effective method for growing magnetite thin films based on a chemical vapour deposition (CVD) process [17].…”
Section: Introductionmentioning
confidence: 99%
“…These unexpectedly small negative MR ratios may be due to the difficulty of preparing Fe 3 O 4 /insulator interfaces. An earlier study experimentally investigating fully epitaxial Fe 3 O 4 / MgO / CoFe MTJs with MgO barrier layer grown at RT obtained a MR ratio of −14% at 293 K. 7 Although this negative MR ratio is the largest RT value that has been reported, in that study, normal MTJs with positive MR ratios up to 10% were also found on the same wafer. Because the sign of the MR ratio is affected by other iron oxides in the vicinity of the interface, such as ferromagnetic ␥-Fe 2 O 3 ͑Ref.…”
mentioning
confidence: 68%